In vitro plant regeneration of Cattleya sp. from Protocorm-Like Bodies (PLBs) using coconut water and activated charcoal - FAUZIYAH HARAHAP; ANITA RASUNA SARI SIREGAR; IDRAMSA IDRAMSA; CICIK SURIANI; SYAHMI EDI; NURUL HUDA PANGGABEAN; ABDUL HAKIM DAULAE; SELVIA DEWI POHAN; AURA ALBIZIA TANJUNG; SUFINA INTAN PERTIWI; ANITA KAIRANI (Smujo International, 2026)
Abstract. Harahap F, Siregar ARS, Idramsa, Suriani C, Edi S, Panggabean NH, Daulae AH, Pohan SD, Tanjung AA, Pertiwi SI, Kairani A. 2026. In vitro plant regeneration of Cattleya sp. from Protocorm-Like Bodies (PLBs) using coconut water and activated charcoal. Asian J Agric 10 (1): g100130. https://doi.org/10.13057/asianjagric/g100130. Cattleya sp. is an ornamental orchid whose seeds lack of endosperm, making natural germination and propagation difficult. In vitro culture using Protocorm-Like Bodies (PLBs) offers an alternative for mass propagation. This study aimed to evaluate the effects of coconut water and activated charcoal on the in vitro regeneration of Cattleya sp. PLBs. A completely randomized design was employed with varying concentrations of coconut water (0, 5, and 10%) and activated charcoal (0, 0.1, 0.2, and 0.3 g/L). Morphological parameters observed included time to shoot emergence, number of leaves, shoots, and roots, as well as shoot color. Data were analyzed using two-way ANOVA. The results showed that coconut water significantly accelerated shoot emergence with 10% of coconut water producing the fastest response (12 days after treatment). Activated charcoal enhanced shoot and leaf formation with 0.3 g/L, producing the highest number of shoot and leaf. Root formation was optimal at lower charcoal concentrations. Overall, the combination of coconut water and activated charcoal significantly influenced PLBS growth and regeneration. These findings indicate that appropriate combinations of organic additives can optimize in vitro regeneration of Cattleya sp. and support efficient orchid propagation.